Prevalence and Antimicrobial Resistance of Enterococcus Species: A Retrospective Cohort Study in Italy - Mariarosaria Boccella; Biagio Santella; Pasquale Pagliano; Anna De Filippis; Vincenzo Casolaro; Massimiliano Galdiero; Anna Borrelli; Mario Capunzo; Giovanni Boccia; Gianluigi Franci (MDPI AG, 2021)
Antimicrobial resistance represents one of the main threats to healthy ecosystems. In recent years, among the multidrug-resistant microorganisms responsible for nosocomial infections, the Enterococcus species have received much attention. Indeed, Enterococcus have peculiar skills in their ability to acquire resistance genes and to cause severe diseases, such as endocarditis. This study showed the prevalence and antimicrobial resistance rate of Enterococcus spp. isolated from clinical samples, from January 2015 to December 2019 at the University Hospital "San Giovanni di Dio e Ruggi d'Aragona" in Salerno, Italy. A total of 3236 isolates of Enterococcus faecalis (82.2%) and Enterococcus faecium (17.8%) were collected from urine cultures, blood cultures, catheters, respiratory tract, and other samples. Bacterial identification and antibiotic susceptibility were performed with VITEK 2. E. faecium showed a high resistance rate against ampicillin (84.5%), ampicillin/sulbactam (82.7%), and imipenem (86.7%), while E. faecalis showed the highest resistance rate against gentamicin and streptomycin high level, but both were highly sensitive to such antibiotics as tigecycline and vancomycin. Studies of surveillance are an important tool to detect changes in the resistance profiles of the main pathogens. These antimicrobial susceptibility patterns are necessary to improve the empirical treatment guideline of infections.